PENGARUH PENGETAHUAN DAN PERILAKU PEMILIHAN MAKANAN JAJANAN ANAK SEKOLAH TERHADAP KEJADIAN PENYAKIT DIARE DI SMA NEGERI 12 SERAM BAGIAN TIMUR - MALUKU - Donny Patty; Henry Sudiyanto; Mohammad Yusuf Alamudi (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
For School children, choosing low-quality snacks is a problem of major concern in society, especially foods that contain dangerous chemicals on the market. Canteens and food sellers at school are important agents that cause children to consume unthelthy food, which can cause diarrhea. This study was to determine the effect of knowledge and behavior in selection school children’s snack on the incidence of disease diarrhea in SMA Negeri 12 Seram Bagian Timur-Maluku. this is a quantitative study with a simple regression analysis design, the sample of the study was taken from class X Studens from two majors of science and social studies with a total of 48 people using a purposive sample technique. The independent variable in this study is the knowledge and behavior of choosing snacks and the dependent variable is the incidence of diarrhea. With the research instrument using a questionnaire. of the study showed that 23 respondents had very high (47,92%) 21 high (43,75%) 3 medium (6,25%) and 1 Low knowledge (2.0%) then in terms of behavior there were 17 respondents with very high (35,42) 23 high (47,92%) 7 medium (14,58%) and 1 behavior (2,08) and in the incidence of diarrhea there were 17 respondents in the categories very high (35,42%) 18 high (37,50%) 10 medium (20,83%) and 1 lo (2,08%).